Axenfeld Rieger Syndrome: A Rare Developmental Disorder - Shilpa Singh; Anurag Narula; Sunil Chakarborty; Sapna Chanana (Delhi Journal of Ophthalmology)
To report a case of Axenfeld-Rieger syndrome which is a rare developmental disorder and to discuss the literature pertaining to it. Clinical data was recorded for a 22 year old male, case of Axenfeld-Rieger syndrome. Patient was put on multiple topical anti-glaucoma medicines and was called for regular followup. Visual acuity of the patient improved from finger counting at 1.5mts both eyes to 3mt both eyes and intraocular pressure was reduced from 28 mm Hg in both eyes to 10 and 12 mmHg in right and left eye respectively. Thus multiple topical glaucoma medicines along with frequent follow-ups can help achieve useful vision in cases of Axenfeld-Rieger syndrome.